Pengaruh Model ARCS dan Motivasi Belajar terhadap Keterampilan Menulis Teks Pidato Persuasif (The Effect of the ARCS Model and Learning Motivation on Persuasive Speech Text Writing Skills) - Inti Ikhlasani; Syahrul Ramadhan; Ahmad Johari Sihes; Norliza Jamaluddin (Indonesian Language Education and Literature, 2023)
This study aims to (1) explain the effect of the ARCS and conventional learning models on writing skills; (2) explain the effect of the ARCS model Attention, Relevance, Confidence, Satisfaction) on writing skills for students who are highly motivated to learn; (3) explain the effect of the ARCS model on writing skills for students with low learning motivation; and (4) explain the interaction between the ARCS learning model with learning motivation towards writing skills. This type of research is a quasi-experiment. Sampling was done by purposive sampling technique. The research samples are class IXB and IXE. The research findings showed (1) the persuasive speech text writing skills of students taught by the ARCS model were higher than students taught by the conventional model for both students with high learning motivation and low learning motivation; and (2) there is an interaction between the ARCS model and learning motivation in influencing persuasive speech text writing skills.Penelitian ini bertujuan untuk (1) menjelaskan pengaruh model ARCS Attention, Relevance, Confidence, Satisfaction) dan model pembelajaran konvensional terhadap keterampilan menulis; (2) menjelaskan pengaruh model ARCS terhadap keterampilan menulis untuk siswa yang bermotivasi belajar tinggi; (3) menjelaskan pengaruh model ARCS terhadap keterampilan menulis untuk siswa yang bermotivasi belajar rendah; dan (4) menjelaskan interaksi antara model pembelajaran ARCS dengan motivasi belajar terhadap keterampilan menulis. Jenis penelitian ini adalah quasi experiment. Pengambilan sampel dilakukan dengan teknik purposive sampling. Sampel penelitian, yaitu kelas IXB dan IXE. Temuan penelitian menunjukkan (1) keterampilan menulis teks pidato persuasif siswa yang diajar dengan model ARCS lebih tinggi daripada siswa yang diajar dengan model konvensional baik pada siswa bermotivasi belajar tinggi maupun bermotivasi belajar rendah; dan (2) terdapat interaksi antara model ARCS dan motivasi belajar dalam memengaruhi keterampilan menulis teks pidato persuasif.